Exploring the Relationships Among Level of Contact, Nature of Contact, and Mental Illness Stigma in Adolescent Girls. (2nd January 2016) - Greenblatt, Amy M.; Pinto, Melissa D.; Higgins, Melinda K.; Berg, Carla J.
Abstract : This study explored the relationship of individuals' level of contact with someone with mental illness, and the nature of that contact, to mental illness stigma in adolescent females ( N = 156). There were no significant associations among stigma and level of contact. The nature of the contact was significantly associated with stigma, such that those who knew someone who received treatment in a psychiatric facility had lower stigma, and those who attributed a deterioration of a past personal relationship to mental illness reported greater stigma.